Project Based Learning Model on Students' Critical Thinking Skills on the Material of Elasticity and Hooke's Law - Lestari, Helmayani; Doyan, Aris; 'Ardhuha, Jannatin; Harjono, Ahmad (Balai Publikasi Indonesia, 2025)
This study aims to determine the effect of the project-based learning model on students' critical thinking skills on elasticity and Hooke's law. The population in this study was all class XI MIPA SMAN 1 Terara. Sampling was carried out using a purposive sampling technique, so that class XI MIPA 1 as many as 30 people as the experimental class and class XI MIPA 3 as many as 30 people as the control class. The type of research used was a quasi-experimental with a nonequivalent control group research design. The instrument used was a descriptive test of 5 questions. Post-test data were analyzed using a normality test using the chi-square formula and homogeneity test using a variance test, then hypothesis testing using a polled variance t-test, because the number of students in the experimental and control classes was the same and the data was distributed homogeneously. This test was conducted to determine whether or not there was an effect of the project-based learning model on students' critical thinking skills. Data analysis shows that the values are 5,90 and 2,00, so that it means there is a positive influence of the project-based learning model on students' critical thinking skills in the material on elasticity and Hooke's law